Delineation of Crohn's Disease Trajectories Using Change in Lémann Index: A Natural History Study. Issue 6 (July 2016) - Bhagya Rao, Bhavana; Koutroubakis, Ioannis E.; Ramos Rivers, Claudia; Colombel, Jean Frederic; Regueiro, Miguel; Swoger, Jason; Schwartz, Marc; Baidoo, Leonard; Hashash, Jana; Barrie, Arthur; Dunn, Michael A.; Binion, David G.
Abstract : Background: Crohn's disease (CD) causes lifelong, progressive bowel damage, which may be quantified using the Lémann Index (LI). We aimed to analyze patterns of LI and its association with 5-year clinical course, in an independent cohort of CD patients. Methods: CD patients with 5-year follow-up from a registry maintained at a tertiary center were included. LI was calculated using a computerized metric from the first (LI1) and last (LI2) clinical encounters during the 5 years. Groups were created based on change in score (LI2-LI1) or the delta Lémann Index (DLI) as showing improvement, no change, or deterioration and used for association analysis with patterns of health care utilization, disease activity, and quality-of-life scores. Results: A total of 363 CD patients with 5-year follow-up formed the study population [median age 43 y (interquartile range (IQR), 33.3 to 55 y); 57% female; median disease duration 12 y (IQR, 3 to 19 y), overall surgical exposure 69.7%]. Median (IQR) LI1, LI2, and DLI were 8 (0 to 54), 9 (0 to 75), and 0 (−22 to –47), respectively. Patients were stratified based on DLI into 3 groups: A: DLI<0; B: DLI=0; and C: DLI>0; which comprised 16.5%, 35.3%, and 48.2% of the cohort, respectively. Patients in group C had significantly higher CD-related surgical exposure, health care utilization, and annual use of steroids and biological agents. DLI showed independent significant positive correlation with perianal disease ( P =0.044), steroid use ( P =0.007), clinical visits ( P <0.001), and new surgeries ( P =0.001). Conclusions: Change in LI over time could function as a marker of disease trajectory for risk substratification and prognostication in CD.